2016
DOI: 10.3892/ijmm.2016.2552
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid enhances the antileukemic effect of cytarabine by triggering cell apoptosis

Abstract: Abstract. Acute myeloid leukemia (AML) is an aggressive clonal malignancy of hematopoietic progenitor cells with a poor clinical outcome. The resistance of leukemia cells to contemporary chemotherapy is one of the most formidable obstacles to treating AML. Combining valproic acid (VPA) with other anti-leukemic agents has previously been noted as a useful and necessary strategy which can be used to specifically induce anticancer gene expression. In the present study, we demonstrated the synergistic antileukemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The effect of the combination of VPA with several drugs in AML has been explored, demonstrating synergy with ATRA [121,122,137,138,139,140], Decitabine [123,124,125], Gemtuzumab ozogamicin (GO) [126], AZA [127], retinoid IIF [128], proteasome inhibitors NPI-0052 or PR-171 [129], Curcumin [130], hydroxiurea or 6-mercaptopurine [131], Dasatinib [132], Bortezomib [133,134], Cytarabine [135,142,143], or the Mouse Double Minute 2 (MDM2) inhibitor Nutlin-3 [136], among others. These combinations induced a synergistic effect on apoptosis and inhibition of cell proliferation of AML cells.…”
Section: Histone Deacetylase Inhibitors (Hdaci): Mechanism Of Actimentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the combination of VPA with several drugs in AML has been explored, demonstrating synergy with ATRA [121,122,137,138,139,140], Decitabine [123,124,125], Gemtuzumab ozogamicin (GO) [126], AZA [127], retinoid IIF [128], proteasome inhibitors NPI-0052 or PR-171 [129], Curcumin [130], hydroxiurea or 6-mercaptopurine [131], Dasatinib [132], Bortezomib [133,134], Cytarabine [135,142,143], or the Mouse Double Minute 2 (MDM2) inhibitor Nutlin-3 [136], among others. These combinations induced a synergistic effect on apoptosis and inhibition of cell proliferation of AML cells.…”
Section: Histone Deacetylase Inhibitors (Hdaci): Mechanism Of Actimentioning
confidence: 99%
“…One of the most widely studied drugs in combination with VPA is ATRA, which has demonstrated anti-leukemic activity in experimental in vitro studies [121,122] but yielded poor responses in several clinical trials in poor-risk or elderly AML patients [137,138,139,140,141]. VPA has been used in combination with Cytarabine, resulting in synergistic anti-leukemic activity in AML cell lines and patient samples and in a murine AML model [135]. In a clinical trial in elderly AML patients, the combination of low doses of Cytarabine with VPA showed good therapeutic activity [142].…”
Section: Histone Deacetylase Inhibitors (Hdaci): Mechanism Of Actimentioning
confidence: 99%
“…It has demonstrated neuroprotective effects against various insults through multiple cellular pathways. In addition, VPA has been shown to have anti-cancer effects against a wide variety of neoplasms [41][42][43][44][45][46][47][48]. The anti-tumor activity of VPA was reported to be attributed to its ability to inhibit histone deacetylase [13,49].…”
Section: Discussionmentioning
confidence: 99%
“…The experiment with the transplantation of glioblastoma multiforme, which had been treated with VA cells three times, demonstrated that animals' survivability increased unlike the control (transplantation of untreated tumor cells to mice) (Hosein et al 2015). Using PCR, it was shown that a combination of VA and cytarabine significantly increased Bax gene expression, suppressed leukemia cell proliferation and led to pathological cells apoptosis (Liu et al 2016). Treatment with using VA also leads to the cell cycle stop in G1-phase by decreasing cyclin D1 (Fortunati et al 2008, Ma et al 2007 and can induce autophagy in certain types of cancer, such as prostate cancer and some kinds of lymphoma, by activating adenosine monophosphate kinase (AMPK) and inhibiting mTOR (Ji et al 2005, Xia et al 2016.…”
Section: Valproic Acid Effect On Tumor Cellsmentioning
confidence: 99%